Kepatuhan Wajib Pajak Melalui Kesadaran Wajib Pajak, Motivasi Wajib Pajak, dan Persepsi Korupsi - Putri Intan Permata Sari; Ebi Abady Putri; Berta Agus Petra; Rindy Citra Dewi (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to examine the effect of taxpayer motivation and perceptions of tax corruption on taxpayer compliance with taxpayer awareness as an intervening variable. The data used in this study are primary data obtained by distributing questionnaires directly to respondents, namely individual taxpayers registered at KPP Pratama Padang Satu. The sampling technique used accidental sampling technique and the analytical method used was multiple linear regression analysis using SPSS version 25. The results of this study indicate that the motivation of taxpayers and perceptions of tax corruption partially have no effect on taxpayer awareness. Taxpayer motivation influences taxpayer compliance. Perceptions of tax corruption and taxpayer awareness partially affect taxpayer compliance. Taxpayer motivation influences taxpayer compliance with taxpayer awareness as an intervening variable. Perceptions of tax corruption have no effect on taxpayer compliance with taxpayer awareness as an intervening variable.